Impact of physical performance and anthropometric characteristics on serve velocity in elite junior tennis players - Fett, J.; Ulbricht, A.; Ferrauti, A. (The Journal of Strength and Conditioning Research, 2020)
This study aimed to investigate the impact of physical performance components and anthropometric characteristics on serve velocity (SV) in elite junior tennis players depending on the sex and age group. A sample of the best 1,019 (male = 625, female = 394) junior squad tennis players of the German Tennis Federation participated in the study involving complex anthropometric measurements (body height, body mass, sitting height, and arm span) and physical tests (e.g., SV, medicine ball throws [MBTs], hand grip strength, push-ups, back extension, countermovement jumps [CMJs], horizontal jumps, 20-m sprint, and tennis-specific endurance). Of all the anthropometric and physical characteristics analyzed, the MBTs (r = 0.49-0.60 male; r = 0.20-0.60 female), hand grip strength (r = 0.43-0.59 male; r = 0.27-0.37 female), arm span (r = 0.37-0.56 male; r = 0.24-0.36 female), body height (r = 0.31-0.52 male; r = 0.26-0.38 female), and body mass (r = 0.44-0.57 male; r = 0.35-0.39 female) were particularly closely correlated with SV. The results of the multiple regression analysis indicated that the combination of selected predictors (e.g., MBTs, grip strength, arm span, and body mass) explained 41-66% of the variance in SV of boys and 19-45%, respectively, for girls. The results reinforce that service speed is dependent on physical abilities and anthropometric characteristics but also strongly on additional factors (i.e., technical components). In particular, the upper-body power/strength is important to the junior players' service, especially in athletes with a greater body height and arm span (i.e., biomechanical advantages), whereas purely lower-body power (e.g., CMJ) is less important. To this effect, talent identification and intervention programs focusing on the specific requirements are recommended.